A PRESENÇA DA ANSIEDADE EM CANDIDATOS A CARTEIRA NACIONAL DE HABILITAÇÃO: POSSÍVEL CAUSA DE REPROVAÇÃO - Antolini, Luana Massoco (2020)
Anxiety can be considered normal when there is a threat to the future and the individual needs to protect himself, which can generate physical and psychological changes, while pathological anxiety prevents the person from doing something. Observing that anxiety is one of the main complaints in individuals who reproval in the driver’s license test, considering the data from Detran-RS, that the approval rate in the driver’s license test is just 44.2%. This study aimed to identify if the anxiety can be one of the main causes of reprovation in candidates for driver’s license. At the beginning of the process, the socio-demographic profile of the candidates was identified, in addition to the application of a questionnaire with questions related or not to anxiety and also the Hamilton Scale. Only for candidates reproved in the driver’s license test, another questionnaire and again the Hamilton scale were applied in order to assess changes in anxiety scores and to assess other factors directly or indirectly linked to anxiety. The survey had a convenience sample of 121 candidates between 18 and 70 years old and were evaluated in greater number in the age group of 20 to 30 years old, female, single, complete high school and family income between one and two minimum wages. Most of the candidates did not declare themselves anxious and the anxiety-related scores obtained with the Hamilton scale indicate improblable anxiety for the majority. At the day of the test, most of the candidates did not use controlled medication or alternative natural medication, and reported that they did not present any body changes in the moment before the test. However, during the test, most candidates reported feeling some change in the body, being significant in candidates who were classified with probable and possible anxiety. Self-reported anxiety changed after reproval, where most candidates report being always anxious. In addition, anxiety-related scores changed significantly after reprovation, from improbable to problable and possible anxiety. The Hamilton scale also evaluates scores related to depression, scores that did not change in the reproved candidates (improblable depression). Based on the findings of this study, it can be concluded that the anxiety observed in the candidates, can be one of the main causes of reprovation, being nomal anxiety, which may be linked to the fact that the candidates are subjected to a test.